Refinement of molecular interaction parameters of AMBER force field for CO 2 and 2-methylimidazolate complexes - P. Puphasuk (2018)
The intermolecular interaction between CO 2 and 2-Methylimidazole has been derived by modifying the parameters of AMBER force field to ab initio single point energies. Each energy is obtained at HF/6-31G(d). The influence of basis set superposition error (BSSE) has been taken into consideration. We found that the BSSE correction is required for obtaining the reliable interaction energies. The Levenberg-Marquardt algorithm is used for parameters refinement. These new parameters are found to be able to represent QM data better than the original AMBER parameters. Copyright © 2012 American Scientific Publishers.